Про задачу описання ситуації на основі прототипів - Kadomsky, K. K.; Kargin, А. А. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2013)
The use of prototypes for situation representation allows solving the situation interpretation problem in modern situational and cognitive control systems. Here the problem of representation of complex situations characterized by the set of incomplete additional descriptions is solved with help of fuzzy prototypes. The case in which the initial information about the situation is a finite set of fuzzy or linguistic estimations of numerical features is addressed. It is proposed to represent a prototype in the form of a fuzzy vector with parametrically defined components. A method of forming prototypes hierarchy based on specification principle, which only requires storing limited set of simple, the most common prototypes, is proposed. Simple prototypes storing is organized in content addressable memory. To increase the memory access rate the problem of efficient distance estimation in the prototype space is solved. Complex composite prototypes are formed dynamically on the basis of activation vector of the simple prototypes. The time complexity of the corresponding algorithm is linearly dependent on the memory capacity.